Plano de Ações Articuladas (PAR) do município de Chapada dos Guimarães de 2007-2017 - Santos, Gilberto Gomes dos (2020)
This study aims at analyzing the influence of the Articulated Action Plan (PAR) for both planning and implementation of the basic education policies of Chapada dos Guimarães town in the period between 2007- 2017. The Articulated Action Plan is an educational policy that aims at enabling both planning and implementation of the public policies targeted to the improvement of the quality of basic education. The programs integrated to PAR cover the following dimensions of the educational policies: educational management, teachers education and school service and professionals support; pedagogic practices and evaluation and physical infrastructure and pedagogic resources. This study is based on a qualitative research established in the theorical-methodological suppositions of the dialectical materialism, developed through documentary analysis and semistructured interviews. The results reveal that the decentralization through municipalization has not obtained the expected success as the autonomy given to the towns in the local educational management, due to the strong centralization executed by the Union in the educational policies implementation. It was observed that, despite the municipality devise the planning by means of PAR, the resources sent by the Ministry of Education (MEC) to the educational programs is a form by which the municipality continue the formulated policies by the federal government, as they do not have both administrative and financial self-sufficiency to implement their own policies. Institutional autonomy difficulty was highlighted in both implementation and monitoring of PAR as patrimony in the local administration, as well as the limitation and little knowledge of the educational managers about the PAR and the Integrated System of Monitoring, Execution and Control (Simec); the lack of flexibility of these systems in assisting the municipality´s specificities. From the above, it is comprehended that, for the municipality to achieve the Target Plan´s objectives for the benefit of the municipality planning and both financial and technical support of MEC in assisting their specific demands, aligning this one that materialize itself by the major education for the educational managers in planning; Simec´s both flexibilization and improvement, mainly, the establishing of the management of collaboration and reciprocity among Union, Estate, Municipality, that make possible financial conditions for the municipality acquire autonomy to both plan and implement its own educational policies respecting the local diversities.